Tropical shrimp aquaculture farms harbour pathogenic Vibrio parahaemolyticus with high genetic diversity and Carbapenam resistance. (November 2020) - Narayanan, Sreejith V.; Joseph, Toms C.; Peeralil, Shaheer; Koombankallil, Reshmi; Vaiyapuri, Murugadas; Mothadaka, Mukteswar P.; Lalitha, Kuttanapilly V.
Abstract: In characterization of food borne pathogens from the environment, assessment of virulence, genetic diversity and AMR are essential preludes to formulate preventive strategies and to combat the spread. This study aimed to identify and characterize pathogenic Vibrio parahaemolyticus in the coastal aquaculture farms of Kerala, India. Twenty-seven β-haemolytic V. parahaemolyticus were isolated from 7 out of 40 farms studied. Among the 27 isolates, 15 possessed the tdh gene and 4 had trh. ERIC PCR and PFGE illustrated the presence of pathogenic isolates that shared genetic similarity with clinical strains. One pathogenic isolate was identified to be multidrug resistant (MDR) and 59% exhibited a MAR index of 0.2 or above. Seventy four percent of the pathogenic isolates were ESBL producers and 3.7% of them were carbapenemase producers phenotypically. This asks for adoption of control measures during farming to prevent the transmission of pathogenic V. parahaemolyticus to the environment and food chain. Highlights: 7 of the 40 coastal aquaculture farms studied harboured pathogenic V. parahaemolyticus . tdh and trh genes were present in 15 and 4 isolates respectively. 59% of the pathogenic isolates showed significant MAR index of 0.2 or above. MDR strain with carbapenam resistance was identified among the pathogenic V. parahaemolyticus isolates. ERIC and PFGE revealed similarity of the environmental isolates with clinical strains.